Biomorphous Silicon Carbide as Novel Loop Heat Pipe Wicks1 . Issue 1 (16th September 2016) - Weisenseel, Bastian; Greil, Peter; Fey, Tobias
Abstract : Biomorphous silicon carbide is tested as a novel wick material for flat evaporator loop heat pipes (LHP). The machinable ceramic gives the possibility to improve the wick performance by macroporous channel networks without closing the structure inherent microporosity. A minimum thermal resistance of 0.4236 °C W −1 is obtained for unmodified SiC at a power input of 200 W. Modification with channels parallel to the evaporating surface results in an improved thermal resistance of 0.3792 °C W −1 . Modification with channels perpendicular to the evaporating surface increases the thermal resistance to 0.4469 °C W −1, but reduces the necessary heat load for stable start‐up from 50 to 25 W. Abstract : The key to enhance the performance of loop heat pipes is to optimize the pore structure of the used porous material (the "wick"). In this work, we present the thermal performance of highly porous biomorphous silicon carbide wicks and demonstrate the possibility to improve the performance by the introduction of macroporous channels in the easily machinable ceramic.